Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
3
Step-by-step explanation:
You substitute the 3, 2 and 7 in for your variables (the letters) and add parentheses ( ) to organize your data and use order of operations (PEDMAS) to solve. So when I did it I but the numbers in (3*3) + (11*2) - (4*7), then solved inside the parentheses to get 9 + 22 - 28 and solved across, 9 + 22 = 31 - 28 = 3. Hope this made sense and helps!
Answer: 16236
Step-by-step explanation:
[tex]f^{3} + 11g - 4h when (f = 3), (g = 2) and (h=7) \\\\(3^{3} + 11^{2}) - 4^{7} = \\ \\\\3x3x3=27\\11x11= 121 \\4x4x4x4x4x4x4= 16384[/tex][tex]27+121-16384= 16236[/tex]
sorry if I'm incorrect I'm 7th grade and thought this looked like something i can do....
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.